Rubella outbreak among workers in three small- and medium-size business establishments associated with imported genotype 1E rubella virus—Shizuoka, Japan, 2015. Issue 46 (27th October 2020) - Kato, Hirofumi; Kamiya, Hajime; Mori, Yoshio; Yahata, Yuichiro; Morino, Saeko; Griffith, Matt; Ikegaya, Asaka; Sahara, Keiji; Furuta, Toshihiko; Okuno, Hideo; Fukusumi, Munehisa; Sunagawa, Tomimasa; et al.
Highlights: Workplace-associated outbreaks of rubella occurred in Japan in 2015. This outbreak was caused by the strains related to the Southeast and East Asian lineage. Vaccine strategy is required because males remain largely susceptible due to unvaccinated. Abstract: On 12 February 2015, a local health department (LHD) in Shizuoka prefecture identified two reported rubella cases in its jurisdiction as employees of the same company. As other employees at the company resided both inside and outside of the health department's jurisdiction, it began collaborating with two additional LHDs and the National Institute of Infectious Diseases to investigate and respond to the outbreak, which subsequently identified cases in two additional companies. We obtained epidemiological, clinical, and outbreak response information from the national epidemiological surveillance of infectious disease system's database, the local health departments, and the associated companies. One specimen for genetic sequencing was collected from each of the three companies. The outbreak included a total of twenty-five cases, with seventeen confirmed and eight probable cases from three companies. Among them, 24 (96%) were male, 22 (88%) were employees of one company (Company X), and none had rubella vaccination history. The median age was 45 years (interquartile range: 40–51). Epidemiological information did not reveal the source of infection nor transmission route. All rubella viruses sequenced from the three specimens were classified into genotype 1E. The nucleotide sequences in the 739 bp-window region were completely identical in two specimens, with only one nucleotide difference in the third specimen. According to phylogenetic analysis, these strains were closely related to the Southeast and East Asian lineage. This rubella outbreak at three companies, ranging in size from small- to medium-size, in Japan occurred among unvaccinated employees aged at least 30 years, most of whom were male. Virologic analyses suggest all cases were infected with the same viral strain imported from Southeast Asia. Similar to these companies, most employees at small- and medium-size businesses in Japan are males with no vaccination history for rubella, which poses a serious risk for associated cases of congenital rubella syndrome (CRS).